Presence of orally administered rice bran oil γ-oryzanol in its intact form in mouse plasma. Issue 12 (23rd November 2016) - Kobayashi, Eri; Ito, Junya; Kato, Shunji; Sawada, Kazue; Matsuki, Midori; Hashimoto, Hiroyuki; Miyazawa, Teruo; Nakagawa, Kiyotaka
Abstract : We prepared OZ concentrate from purified rice bran oil (Rice Oil OZ) and carried out chromatography-mass spectrometry analysis of plasma samples from mice after oral administration of the Rice Oil OZ. Abstract : Although the beneficial effects ( e.g., lipid-lowering activity) of γ-oryzanol (OZ), a mixture of ferulic acid esters of plant sterols and triterpene alcohols, have been extensively investigated, few studies have evaluated the absorption and metabolism of OZ. Moreover, it is unclear whether OZ, once ingested, is directly absorbed by the intestine into the bloodstream at a sufficient level to exhibit activity. Here, we prepared OZ concentrate from purified rice bran oil (Rice Oil OZ), determined the concentration of OZ in the preparation (cycloartenyl ferulate equivalent concentration; 52.2%), and then carried out chromatography-mass spectrometry analysis of plasma samples from mice after oral administration of Rice Oil OZ. The OZ concentrations of plasma from the control (vehicle-treated) mice were low (trace levels); however, at 5 h after a single oral administration of the Rice Oil OZ (600 mg per kg body weight), the levels significantly increased, reaching 17.6 ng mL −1 for cycloartenyl ferulate, 28.2 ng mL −1 for 24-methylenecycloartanyl ferulate isomers, 15.6 ng mL −1 for campesteryl ferulate, and 5.1 ng mL −1 for β-sitosteryl ferulate, respectively, expressed in equivalence of cycloartenyl ferulate in plasma. These results provided the first mass spectrometric evidence suggesting that a portion of orally administered OZ is directly absorbed by the intestine and is present in the intact form in plasma. The presence of a significant amount of OZ in its intact form in plasma may explain the beneficial effects of OZ in vivo .